Morphological dependence of charge generation and transport in blended polyfluorene photovoltaic devices - Snaith, H; Friend, R (2004)
We present a compositional analysis of the phase separation, nano-structure and electrical performance of blended hole-accepting and electron-accepting polyfluorene derivatives, in films and in photovoltaic devices. We use varying molecular weights to vary the thin film morphology, without altering the blend composition. We show that photoluminescence quenching is insensitive to variations in the blend morphology but the photovoltaic quantum yield is strongly dependent on morphology. This indicates that charge transport, and not charge generation, is the factor that limits device performance. We develop a model for the charge transport within a meso-scale phase separated film and estimate the distance which charges can travel within the minor component of each phase. (C) 2003 Elsevier B.V. All rights reserved.